Creation of Two‐Dimensional Electron Gas and Role of Surface Donors in III‐N Metal‐Oxide‐Semiconductor High‐Electron Mobility Transistors. Issue 24 (14th November 2018) - Gucmann, Filip; Ťapajna, Milan; Pohorelec, Ondrej; Haščík, Štefan; Hušeková, Kristína; Kuzmík, Ján
Abstract : The role of surface donors at the oxide/semiconductor interface of III‐N metal‐oxide‐semiconductor (MOS) high‐electron mobility transistors (HEMTs), by creating a two‐dimensional electron gas (2DEG) and the device performance, are investigated. Al2 O3 /GaN/AlGaN/GaN MOS HEMTs show the surface donor density ( N d, surf ) of 2.2 × 10 13  cm −2, which is increased up to 3.4 × 10 13  cm −2 after post‐deposition annealing. In the latter, surface donors fully compensate the surface polarization charge and the HEMT threshold voltage decreases substantially with the oxide thickness. On the other hand, an open‐channel drain current is found to be independent of N d, surf, while marginal trapping is completely removed when N d, surf increases with annealing. Consequently, ionized surface donors behave like a fixed charge and are clearly distinguishable from trapping states. Open‐channel 2DEG densities of ≈1.1 × 10 13  cm −2 are extracted from capacitance–voltage measurements. Similarly, recent data on enhancement‐mode HfO2 /InAlN/AlN/GaN MOS HEMTs are analyzed where N d, surf is reduced down to 1 × 10 13  cm −2 while 2DEG densities reach ≈2.7 × 10 13  cm −2 . It is suggested that under the open‐channel condition, 2DEG is supplied also by an injecting source contact if N d, surf is lower than the QW polarization charge. Our charge quantifications are supported by calculating energy‐band diagrams. Abstract : In III‐N metal‐oxide‐semiconductor (MOS) high‐electron mobility transistors (HEMTs) it is found that i) ionized surface donors behave like a fixed charge and are distinguishable from trapping states; ii) open channel drain current is independent on the surface donor density; and iii) 2DEG is populated by electrons transferred from surface donors (if not completely eliminated) and injecting source contact.